Sensory Characteristics and Antimicrobial Activities of Soft Candy with Essential Basil (Ocimum Sanctum L.) Against Candida Albicans and Streptococcus Mutans - Maria Belgis; Giyarto; Malvira Mega Febriyanti; Ahmad Nafi; Dyah Ayu Savitri; Andrew Setiawan Rusdianto (Newinera Publisher, 2022)
Soft candy is a type of confectionery product that has a chewy texture. Chewing candy can stimulate the activity of salivary secretion, thus it supports the release of active compounds in the mouth. Essential oil contains of active compounds that are able to control bacteria growth that may cause bad breath. The purpose of this study was to observe the antimicrobial activity of soft candy with the addition of basil essential oil (0.2%, 0.4%, 0.6%, and 0.8%) against Streptococcus mutans and Candida albicans and to determine the most acceptable candy by consumers. Parameters of the research observations included antimicrobial activity with solid diffusion and dilution methods, descriptive sensory test with RATA test and acceptability test (aroma, taste, mouthfeel, aftertaste, and overall), and effectiveness test. The results showed that the addition of 0.4% basil essential oil in soft candy performed the highest effectiveness value (0.71). The effectiveness value was obtained from the results of the inhibition zone (disc) test, and the results of the acceptability test. Therefore, from the research, it can be concluded that soft candy with basil essential oil has a great potential to be utilized as antimicrobial agent to overcome mouth problems.